Temporal and spatial changes in bone accrual, density, and strain energy density in growing foals. (March 2020) - Moshage, Sara G.; McCoy, Annette M.; Polk, John D.; Kersh, Mariana E.
Abstract: Bone adaptation is in part driven by mechanical loading, and exercise during youth has been shown to have life-long benefits for bone health. However, the development of early exercise-based interventions that reduce the incidence of fractures in racing horses is limited by the lack of characterization of normal development in growing bone. Previous efforts to quantify bone development in the horse have relied on repeated radiographs or peripheral quantitative computed tomography scans, which are limited in their assessment of the entire bone. In this study, we acquired computed tomography scans of three Standardbred trotting colts longitudinally between 2 and 12 months of age. Finite-element models were constructed of the left forelimb proximal phalanx and used to assess strain energy density during quiet standing. Growth related changes in mineral density and bone area fraction in the distal epiphysis, mid-diaphysis, and proximal epiphysis were evaluated. Mineral density and bone area fraction uniformly increased in the diaphysis and strain energy density was constant during growth, indicating adaptation to quiet standing. Bone mineral density and bone area fraction increased in the medial quadrant of the proximal epiphysis but not in the fracture-prone lateral quadrant. The data presented provides a benchmark of normal growth trajectories that can be used to evaluate the effect of training regimens during growth. Graphical abstract: Image 1 Highlights: Equine proximal phalanx bone density and area changes depend on spatial location. Proximal phalanx diaphysis has adapted to sustain standing loads. Fractures to the proximal phalanx occur in a region with least changes during growth.